KURDISH STUDENTS’ PERCEPTIONS TOWARD COMMUNICATIVE LANGUAGE TEACHING AT A UNIVERSITY IN KURDISTAN REGION IRAQ - Abdullah, Berivan Mohammed Ahmed (European Scientific Journal, ESJ, 2015)
This is a small scale piece of research that has been conducted to investigate about the Kurdish students’ perceptions of CLT in Kurdistan. The samples involved in this study were 40 Kurdish undergraduate students; 6 out of these 40s were interviewed via skype. The participants were chosen based on their knowledge regarding CLT. These students have been taught the CLT principles for one year and for almost three years they have been taught through CLT. This study was collected by a mixture of qualitative and quantitative data through using a set of questionnaires and semi-structured interviews. This was done in order to find the answer to three research questions which are: (1) what are students’ attitudes toward CLT? (2) Do students think that authentic materials should be used by teachers in English classes? (3) What are the challenges that Kurdish students face when they are taught through CLT method? The findings of the study revealed that students have a positive attitude regarding the use of CLT, as it contributed much to the real world language. Moreover, the results showed that the students are in favour of the use of the authentic materials because they are more interesting than other materials. However, some challenges might face the teachers and the students while implementing CLT in Kurdistan context, such as: lack of authentic materials, lack of teachers’ knowledge, grammarbased exams and students’ proficiency level. Therefore, the findings also revealed that these difficulties can be tackled and by that this approach will work more properly in Kurdistan.